Smart window blinds system - Ng, Siew Ming (2016)
LabVIEW is a visual programming platform developed by the National Instruments and it has been widely used in the industries and in education. For the Final Year Project (FYP), two projects were done using the LabVIEW application - An undergraduate Year 2 Project module EE2073 Introduction to EEE Design and Project E-learning video series and the innovation of the Smart Window Blinds System.